2022
DOI: 10.1590/1678-7757-2022-0330
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of furcal perforation management using Mineral Trioxide Aggregate and Biodentine: a systematic review

Abstract: Furcal perforation is an iatrogenic or pathologic communication between the pulp chamber floor and the alveolar bone. The outcome of perforation sealing depends greatly on the tissue compatibility and bioactivity and sealing properties of the repair materials. Mineral trioxide aggregate (MTA) and Biodentine are currently the most used materials to treat this condition.The present systematic review aimed to report the treatment outcome of repaired furcal perforation using MTA and Biodentine and identify whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…34 The formation of hydroxyapatite on the surface of MTA due to its bioactivity might also have contributed to this outcome. 35 Although the literature supports the positive effects of CSCs on treatment outcome, 33,36 it should be noted that because perforation is a procedural accident, it is almost impossible to provide similar preoperative conditions for all cases. A recent clinical trial with a small sample size found that both MTA and Biodentine were suitable materials for perforation repair, but Biodentine was less capable of inducing cementum regeneration compared with MTA.…”
Section: Perforation Repairmentioning
confidence: 99%
“…34 The formation of hydroxyapatite on the surface of MTA due to its bioactivity might also have contributed to this outcome. 35 Although the literature supports the positive effects of CSCs on treatment outcome, 33,36 it should be noted that because perforation is a procedural accident, it is almost impossible to provide similar preoperative conditions for all cases. A recent clinical trial with a small sample size found that both MTA and Biodentine were suitable materials for perforation repair, but Biodentine was less capable of inducing cementum regeneration compared with MTA.…”
Section: Perforation Repairmentioning
confidence: 99%
“…In some reports, Biodentine produced a better seal than MTA, whereas other studies failed to confirm any superiority of Biodentine or found it to be inferior to MTA when filling the retrograde cavities. A recently published meta-analysis showed that there is a lack of scientific evidence for the superiority of Biodentine over MTA as a retrograde filling material in apical surgery [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of aluminum may affect the efficiency of the reaction, it may also decrease its biocompatibility and lengthen the setting time. Among tested materials, aluminum is present in MTA-type materials, but fully synthetic Biodentine does not contain it [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…), with citation analysis, serving as the main tool for assessing the importance of scientific articles. For its part, the field of scientometrics examines the numerical aspects of science and technology through communication [28][29][30] . That is, exemplifying the use of indicators for research and regulatory management, including citation, counting and delimitating scientific fields.…”
Section: Introductionmentioning
confidence: 99%